2013
DOI: 10.1371/journal.pone.0063213
|View full text |Cite
|
Sign up to set email alerts
|

Small GTPase Rab40c Associates with Lipid Droplets and Modulates the Biogenesis of Lipid Droplets

Abstract: The subcellular location and cell biological function of small GTPase Rab40c in mammalian cells have not been investigated in detail. In this study, we demonstrated that the exogenously expressed GFP-Rab40c associates with lipid droplets marked by neutral lipid specific dye Oil red or Nile red, but not with the Golgi or endosomal markers. Further examination demonstrated that Rab40c is also associated with ERGIC-53 containing structures, especially under the serum starvation condition. Rab40c is increasingly r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 44 publications
1
31
2
Order By: Relevance
“…Thus, it is highly possible that rather than promoting conventional membrane traffic in melanocytes Rab40C mediates recognition of Varp by a Cullin E3 ubiquitin ligase complex. However, we cannot completely rule out the possibility that Rab40C (or other Rab40 isoforms) has an additional membrane trafficking function(s) in melanocytes, the same as in other cell types ( Jacob et al, 2013 ; Tan et al, 2013 ).…”
Section: Discussionmentioning
confidence: 97%
“…Thus, it is highly possible that rather than promoting conventional membrane traffic in melanocytes Rab40C mediates recognition of Varp by a Cullin E3 ubiquitin ligase complex. However, we cannot completely rule out the possibility that Rab40C (or other Rab40 isoforms) has an additional membrane trafficking function(s) in melanocytes, the same as in other cell types ( Jacob et al, 2013 ; Tan et al, 2013 ).…”
Section: Discussionmentioning
confidence: 97%
“…1B, lanes 1-4), suggesting that the localization rather than the expression level of Rab18 was altered by OA treatment. Since Rab18 was previously identified to be localized between ER and LDs by immunogold-EM [18,24], an ER marker protein Sec61β was co-transfected with Rab18 to determine if the LD-associated Rab18 was translocated from ER. Result in Figure 1C showed that Rab18 was co-localized with Sec61β strongly before OA treatment, while the co-localization of these two proteins was disrupted by OA treatment.…”
Section: Recruitment Of Rab18 From Er To Lds During Oa-induced Ld Growthmentioning
confidence: 99%
“…Rab proteins are the major regulators of membrane trafficking and circulate between active form (GTP-bound) and inactive form (GDP-bound). The LD-associated Rab proteins mainly take part in LD formation, LD fusion and the interactions between LD and other organelles [24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…In mammalian cells, Rab40c, but not Rab40a or Rab40b, has been shown to be associated with the ER‐Golgi intermediate compartment (ERGIC) and is present on the surface of LDs (Tan et al, ). RNAi‐mediated depletion of Rab40c decreases LD size, suggesting that Rab40c is involved in LD biogenesis.…”
Section: Ld‐associated Rab Proteinsmentioning
confidence: 99%
“…Upon overexpression, Rab40c induces LD clustering, an effect dependent on the SOCS box remaining intact. Rab40c forms homodimers or homooligomers and, through its SOCS box domain, directly interacts with Tip47 (Tan et al, ). It is likely that homodimers or homooligomers of Rab40c act as a tethering factor to link two or more LDs via Rab40c and Tip47 interaction, eventually leading to grape‐like LD aggregates.…”
Section: Ld‐associated Rab Proteinsmentioning
confidence: 99%